Effect of Peptide Application and Dosage of NPK Fertilizer on the Growth and Yield of Shallot Plants (Allium ascalonium L. var. Bima Brebes) - Modesta Todo; Ni Komang Alit Astiari; Anak Agung Ngurah Mayun Wirajaya (Warmadewa University Press, 2026)
This study aims to determine the effect of peptide application with NPK fertilizer dosage on the growth and yield of onion plants (Allium ascalonium L. var. Bima Brebes). The research was carried out in February – May 2025, which is located at the green house of the Faculty of Agriculture, Science and Technology, Warmadewa University, East Denpasar District, Denpasar City with an altitude of 40 meters above sea level. The design used in this study is a Group Random Design (RAK) with 2 factors arranged factorarily. The first factor of peptide (P) consists of 3 levels of concentration, namely P0 (0 ml 111), P1 (2 ml 1-1) and P2 (4 ml 1-1). The second factor is NPK fertilizer (N) which consists of 4 dose levels, namely N0 (0 kg ha-1), N1 (100 kg ha-1), N2 (200 kg ha-1), N3 (300 kg ha-1). Thus, there are 12 combination treatments that are repeated 3 times, so that 36 polybags are needed. From the results of the study, it was found that the interaction between peptides and NPK fertilizers had a real effect on almost all the variables observed except for the variables of the number of seedlings, the number of tubers and the dry weight of the tuber oven per clump had an unreal effect. The highest fresh weight of tubers per clump was obtained at the interaction between the treatment of 4 ml 1-1 peptide and the treatment of 200 kg ha-1 (P2N2) NPK fertilizer dose which was 20.63 g, an increase of 98.37% when compared to the treatment without peptide and without NPK (P0N0) dose of 10.40 g. Keywords : Shallots, peptides, NPK and yield